Effect of Media Sterilization and Inoculum Dosage on Ectomycorrhizae Formation and Shorea selanica Blume. Growth - Sri Wilarso Budi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
The objectives of this research were to examine the effects of soil media sterilization and the dosage of mycorrhizal inoculum on mycorrhizal development and function and plant growth. Shorea selanica seedlings were inoculated with different ectomycorrhizal soil inoculum dosage and grown in non-sterile and sterile soil. Ectomycorrhizal soil inoculum were collected from under Shorea pinanga tress in Silviculture laboratory. Soils used were infertile acid soils collected from field sites in Jasinga, Bogor. Mycorrhizal inoculation improved the growth of S.selanica seedlings more than on sterile soil medium. The uninoculated seedlings exhibited stunted growth typical of P deficiency both in sterile and unsterile soil. Height at 16 weeks was significantly taller in non-sterile than in sterile soil. A significant interaction effect of inoculation and soil sterilization on height, diameter, shoots and roots biomass at harvest was observed. Mycorrhizal inoculum dosage had a varied effect on mycorrhizal formation. Root colonization was significantly greater in non-sterile soil than in sterile soil in all inoculum dosage.